Places, Chains, and Plates: Governing Transitions in the Shrimp Aquaculture Production-Consumption System - Lebel, L.; Lebel, P.; Garden, P.; Dao, H. G.; Khrutmuang, S.; Nakayama, S. (2012)
The shrimp production-consumption system is governed by a diverse and dynamic array of actors each drawing on institutions at various levels, from local through national to international. But, for the most part, the politics of consumption (plates), chains, and places are disconnected. Instead, shrimp producers face a myriad of institutional and consumer demands and the sustainability of the shrimp aquaculture production-consumption system is not merely a technical problem to be solved by better site selection and management of ponds. Instead, campaigns for, and against, consuming certain kinds of shrimp are launched in remote corners of the globe and standards, codes, and quality assurance schemes are developed and promoted by equally diverse set of actors, to guide and regulate practices of shrimp farmers and food processors. Furthermore, most initiatives take place with little or no consultation with shrimp farmers or the communities living in shrimp growing areas. Efforts to improve sustainability will require much greater attention to ways different stakeholders, in particular, shrimp farmers and affected communities in growing areas, are brought together with other actors, to deliberate and assess impacts, and to negotiate fairer distribution of risks and benefits in a sustainable production-consumption system. Associations based in producer locales and emerging platforms that bridge these arenas would be a good place to start.